(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article problematizes, from an artistic intervention realized in downtown Florianópolis city (Santa Catarina / Brazil), some tensions between past and present and between memory and forgetfulness, all of them constituents of town. The performance discussed in this paper is named Landscape Part, and was presented on a city avenue, where there used to be a river. Providing a breach to an aesthetic relation with urban space instigates the view to what is insignificant and what has been forgotten; proposes to tense the past and the present, the acceleration, the noise and the pauses, the silence contemplation. Instigates to listen to what still resonates in the city from submerged layers stories, a proposal that makes visible the dislocating potency of art.